Socially Assistive Robot for Stroke Rehabilitation: A Long-Term in-the-Wild Pilot Randomized Controlled Trial - Ronit Feingold-Polak; Oren Barzel; Shelly Levy-Tzedek (IEEE, 2024)
Socially assistive robots (SARs) have been suggested as a platform for post-stroke training. It is not yet known whether long-term interaction with a SAR can lead to an improvement in the functional ability of individuals post-stroke. The aim of this pilot study was to compare the changes in motor ability and quality of life following a long-term intervention for upper-limb rehabilitation of post-stroke individuals using three approaches: 1) training with a SAR in addition to usual care; 2) training with a computer in addition to usual care; and 3) usual care with no additional intervention. Thirty-three post-stroke patients with moderate-severe to mild impairment were randomly allocated into three groups: two intervention groups – one with a SAR (ROBOT group) and one with a computer (COMPUTER group) – and one control group with no intervention (CONTROL group). The intervention sessions took place three times/week, for a total of 15 sessions/participant; The study was conducted over a period of two years, during which 306 sessions were held. Twenty-six participants completed the study. Participants in the ROBOT group significantly improved in their kinematic and clinical measures which included smoothness of movement, action research arm test (ARAT), and Fugl-Meyer upper-extremity assessment (FMA-UE). No significant improvement in these measures was found in the COMPUTER or the control groups. 100% of the participants in the SAR group gained improvement which reached – or exceeded – the minimal clinically important difference in the ARAT, the gold standard for upper-extremity activity performance post-stroke. This study demonstrates both the feasibility and the clinical benefit of using a SAR for long-term interaction with post-stroke individuals as part of their rehabilitation program. Trial Registration: ClinicalTrials.gov NCT03651063.